Beyond methods and models. Semiotics as a distinctive discipline and an intellectual tradition - Sonesson, Göran (Signs - International Journal of Semiotics, 2008)
Such familiar characterisations of semiotics as being a method, a model, an interdisciplinary perspective, or a philosophical movement are inadequate, because semiotics itself comprehends many models, methods, and philosophical perspectives, and it is just one of the many enterprises which may be seen as occupying a space intermediate to the traditional sciences. Semiotics must be considered a science in its own right, defined by a particular point of view, rather than a domain of reality. As such it is in many ways comparable to cognitive science. A distinct advantage of cognitive science is being by definition a confluence of different research traditions, whereas semiotics has long been hampered by the autonomy postulate. On the other hand, cognitive science still seems to be stuck in an epistemological impasse, just as semiotics was at the time of structuralism. Cognitive semiotics could be a promising way out of both quandaries.